Policy Dynamics of Regional Regulation Number 12 of 2010 on Spatial Planning in Pasuruan Regency: A William N. Dunn Evaluation - ony syahrial; Aminullah Aminullah (PERSEPTIF: Jurnal Ilmu Sosial dan Humaniora, 2026)
This study analyzes the policy dynamics of Regional Regulation Number 12 of 2010 concerning the Regional Spatial Plan (RTRW) of Pasuruan Regency for 2010 to 2029, focusing on the conversion of conservation land for development. As one of East Java's strategic growth areas, Pasuruan Regency faces increasing pressure to balance economic development and environmental sustainability. The novelty of this study is the application of William N. Dunn's policy evaluation framework to assess long-term spatial planning implementation and identify governance gaps. A descriptive qualitative approach was employed. Data were collected through observation, documentation, and in-depth interviews with representatives of Bapperida, the Public Works and Spatial Planning Office, ATR/BPN, and environmental organizations. Data were analyzed using interactive qualitative analysis through data condensation, data display, and conclusion drawing and verification. The evaluation covered effectiveness, efficiency, adequacy, and equity. The findings reveal significant implementation gaps. The regulation has not effectively controlled conservation and agricultural land conversion, while OSS and KKPR implementation remains constrained by outdated spatial data, weak inter-agency coordination, and limited monitoring. The regulation is also inadequate to address development pressures, and its benefits remain unevenly distributed. The study recommends revising regional spatial regulations, strengthening coordination, improving spatial data governance, enhancing monitoring and law enforcement, and expanding public participation to support adaptive and sustainable spatial planning.